1997
DOI: 10.1136/bmj.314.7078.414
|View full text |Cite
|
Sign up to set email alerts
|

Young people, alcohol, and designer drinks: quantitative and qualitative study

Abstract: Objective: To assess decleration and acceleration in the disease process in the initial phase of epsilepsy in children with new onset tonic-clonic seizures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
50
0
4

Year Published

2001
2001
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(57 citation statements)
references
References 16 publications
3
50
0
4
Order By: Relevance
“…Moreover, alcohol consumption increased markedly from the youngest to the oldest age group. Fortyone percent of 15-y-olds drank alcohol at least once a week, in comparison with 21% of 15-y-old participants in a British sample (Hughes et al, 1997). The Finnish Cohort Study reported a mean daily ethanol intake less than 1 g in this age group (A Ê kerblom et al, 1985).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, alcohol consumption increased markedly from the youngest to the oldest age group. Fortyone percent of 15-y-olds drank alcohol at least once a week, in comparison with 21% of 15-y-old participants in a British sample (Hughes et al, 1997). The Finnish Cohort Study reported a mean daily ethanol intake less than 1 g in this age group (A Ê kerblom et al, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…The Finnish Cohort Study reported a mean daily ethanol intake less than 1 g in this age group (A Ê kerblom et al, 1985). Social and psychological roots of this problem have been studied by qualitative research (Hughes et al, 1997). At 12 ± 13 y, adolescents try any drink to have new experiences.…”
Section: Discussionmentioning
confidence: 99%
“…Research indicates mainly that alcopops have a positive and attractive image among adolescents [7,28,29] and have become one of the most popular alcoholic beverages among adolescents, particularly girls, in established market economies in Europe [e.g. 12, [30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…12, [30][31][32][33][34][35]. The preference for alcopops seems to be a transient behavior that decreases with age [28] and alcopops rarely remain the most preferred alcoholic beverage at older ages [36,37]. A preference for alcopops at younger ages, however, cannot be equated with earlier onset of drinking or drunkenness; we failed to find studies on earlier onset in our literature search.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation